Strategy for Developing Local Chicken - Sofjan Iskandar (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2006)
Chicken industry in Indonesia offer jobs for people in the village areas . The balance in development industry of selected and local chicken has to be anticipated as there has been threat of reducing importation of grand parent stock of selected chicken due to global avian influenza . In the mean time, high appreciation to the local chicken has been shown by the existence of local chicken farms in the size of business scale . For local chicken business, the government has been built programs, projects, and infrastructures, although the programs and projects were dropped scattered in to several institutions, which were end up with less significant impact to the people. Therefore, it is the time that the government should put more efforts to integrate various sources . focusing in enhancing local chicken industry . Key words : Local chicken industry, synergism, government programmes